Estimation of the Peak Discharge in the Arab River basin in Lattakia, Syria by the modified experimental Talbot method TMT - برجيه, دارين (Latakia University Journal -Basic Sciences Series, 2024)
The lack of continuous hydrological records is one of the biggest challenges in managing surface basin water resources, especially when studying floods and the water installations. Therefore, many hydrological researchers applied experimental equations to estimate the peak flow values, as a basic parameter that plays a key role when establishing water projects in the absence of hydrological measurement stations. The modified experimental Talbot method TMT is one of the most famous of these equations, which was applied in this study to estimate the peak flow values ​​in the Arab River basin using GIS software and building purpose maps (geomorphological coefficient, slope, shape, drainage …) and processed to obtain a map of the distribution of the estimated peak flow values, It was found that it ranged on average between (2.5 m3/s) with a return period (5 years) and a maximum of (30 m3/s) with a return period (100 years), The study also showed that the higher values ​​of the estimated flow peak are concentrated in the recharge area in the Arab River Basin, while the lower values ​​are concentrated in the drainage area, which reduces the possibility of flooding.